Photocatalytic Scheme with External Magnetic Field on Coffee Waste in Hydrogen Production - Alphanoda, Abid Fahreza; Prasetyo, Eko; Broto, Wisnu (Journal of Mechanical Engineering Science and Technology (JMEST), 2023)
Photocatalytic is considered a deadlock-breaking technology for renewable energy and lowering environmental pollutants. Photocatalytic efficiency efforts are improved by activating the photocatalyst to introduce an external magnetic field. This review highlights recent breakthroughs by comparing original coffee waste, activation of coffee waste with the addition of catalysts, and manipulation of spin electrons by applying external magnets. Characterization was done with FTIR to look at chemical bonds, UV-Vis with Tauc's Relation approach to measure bandgap, and material morphology using SEM EDX. The increase in photocatalyst activation aligns with the decrease in bandgap value. The rate of decline in bandgap is in line with the rate of acceleration of hydrogen production. Adding an external magnetic increases hydrogen production up to 1.5 times greater than the original photocatalytic.